Sustentabilidade de cidades, inovação e competitividade - Explorando conceitos no caso Brasil - Morgado, Eduardo Martins [UNESP] (My University, 2012)
Competitiveness is the basis of economic progress of a country. Innovation is a cornerstone of competitiveness. The competitiveness of the countries has been assessed by studies of competitiveness through a comprehensive set of indicators, which year after year evolve and expand, with the incorporation of new indicators. Stands out in this expansion the integration of new indicators related to sustainability of cities. This short article will explore the concepts of Competitiveness, Innovation and Sustainability, and based on the description of the methodology of two major studies on Competitiveness, will demonstrate the growing importance of sustainability indicators for cities have been given for these studies. To illustrate the results of studies show Brazil. And finally, will seek to highlight the role of Information and Communication in this context. © 2012 AISTI.
Sustainability of cities, innovation and competitiveness - Exploring concepts in case Brazil
Keywords: Innovation; Studies on Competitiveness; Sustainable Cities; Economic progress; Information and communication; Sustainability indicators; Sustainable cities; Information systems; Sustainable development; Competition